Mengapa Mahasiswa Sering Menunda? Tinjauan dari Perspektif Bimbingan dan Konseling - Zea Apila Natasya; Alysa Azzahra; Nadia Purba; Uli Makmun Hasibuan (Kampus Akademik Publiser, 2026)
Academic procrastination has become a chronic phenomenon among university students, which is frequently normalized in digital spaces. This study aims to explore the psychological dynamics behind students' procrastinating behavior and formulate solutions from the perspective of Guidance and Counseling. The research method employed is qualitative, utilizing library research and digital content analysis. Data sources were gathered from accredited scientific journal articles (2021–2026) and student narrative trends on social media platforms such as Twitter, TikTok, and Instagram. The results indicate that academic procrastination is not merely a matter of poor time management, but rather a manifestation of self-regulation failure and emotional dysregulation. Students use procrastination as an immediate mood repair coping strategy to avoid negative emotions, anxiety, and fear of failure driven by cognitive distortions like irrational perfectionism. Social media further reinforces this behavior through Social Learning Theory, which normalizes cramming. In conclusion, addressing procrastination requires counseling interventions that target cognitive roots. The Cognitive Behavioral Therapy (CBT) approach through cognitive restructuring techniques is highly recommended for university counselors to reshape students' irrational thoughts and restore their self-regulation capacities.